Effect of my fit trainer for balance rehabilitation in chronic stroke patient: a case study - Patil, Abhilasha B.; Thorat , Komal D. (International Journal of Research in Medical Sciences, 2023)
Stroke is the third most common cause of death in the world and most common cause of adult disability of the survivors. Balance problems in stroke is very common, and they have been implicated in the poor recovery of activities of daily living (ADL) and mobility and an increased risk of falls. They also have altered in body weight distribution patterns, so that less body weight is taken through the weaker leg have smaller excursions when moving their weight toward the base of support, mostly in the direction of the weaker leg. My fitness trainer (MFT) balance board consists of a uniaxial unstable platform with an integrated sensor, which records all discrepancies in the plane. A 30-year-old female who has history of stroke 4 year ago has chief complain of weakness of upper limb and lower limb and unable to maintain dynamic balance. In this study we assessed the patient on berg balance scale and my fit trainer balance board with pre score and post score which shows significant improvement in results. The Berg balance scale measure score from 37/56 pre-treatment to 48/56 post treatment which shows significance increase in berg balance scale. The MFT balance board measure score from 4.2 disappointed stability in 30 seconds pre-treatment and 3.4 improve stability in 120 seconds post treatment which shows significance increase in MFT balance board. It concluded that there is effect of MFT to improve balance in chronic stroke patient.